When learning with SLD is a hard challenge: a complex perspective on teacher-student relationships in primary school - Florio, Eleonora; Cornaggia, Alessia; Pianta, Robert C.; Castelli, Ilaria; Caso, Letizia (Frontiers in Psychology, 2025)
IntroductionThe growing body of research highlighting the importance of a positive and supportive student-teacher relationship underscores the need to investigate whether pupils’ needs and teachers’ educational stance may shape the potential protective role of the student-teacher relationship. In line with our hypotheses, we investigated whether the presence of a Specific Learning Disorder (SLD) diagnosis, together with pupils’ and teachers’ demographic characteristics, may affect how both teachers and pupils perceive the quality of their relationship. We also examined teachers’ beliefs and attitudes toward SLD diagnoses and their educational stance, expecting that more adultcentric and authoritarian approaches may increase relational challenges when managing the complexity associated with SLD diagnoses.MethodsThe present work addresses these aims, taking into account pupils’ and teachers’ perspectives on relational quality, teachers’ attitudes and beliefs regarding the rising number of SLD diagnoses in schools, and teachers’ agreement with the Adultcentric paradigm and Bleak Pedagogy. The study involved 66 Italian primary-school teachers and 110 Italian primary-school pupils, who completed validated questionnaires on student-teacher relationship quality, teachers’ attitudes toward SLD diagnoses, and educational stance. Data were analyzed through correlations, paired-sample t-tests, and linear mixed-effects models (LMMs) to examine associations between teachers’ beliefs, pupils’ reports, and perceptions of relational quality.ResultsResults show that the student-teacher relationship may be partly influenced by the presence of an SLD diagnosis. The perceived levels of “Closeness” and “Dependency” were significantly higher when teachers described relationships with a pupil diagnosed with an SLD, compared to their descriptions of the relationship with an undiagnosed pupil with poor school performance.DiscussionParticipants’ agreement with Adultcentrism and Bleak Pedagogy was associated with relationship quality and perceptions of SLD diagnosis, highlighting the substantial unsuitability of such educational stances with our evolving culture and society. Implications for intervention and future research are discussed.